Treatment of industrial waste water using Water hyacinth (Eichornia crassipus) and Duckweed (Lemna minor): A Comparative study - R. Bhutiani; N. Rai; N. Kumar; M. Rausa; F. Ahamad (Environment Conservation Journal, 2019)
As we all know that water is essential to all forms of life and makes up about 70% of the human body weight. Due to the direct link of water quality with human welfare, the quality of water is of vital concern. Industrialization plays major role in the development of a country’s economy. However, these plants and industries generate hazardous by-products and discharge them directly or partially treated into the environment which contaminates the surface water, ground water and soil causing a great threat to the life of human beings, animal and plants. In the present investigation an attempt has been made to identify the potential of water hyacinth (Eichornia crassipus) and Duckweed (Lemna minor) for the treatment of industrial waste water generated from Dehradun industrial area using phytoremediation technology on the basis of different physicochemical parameters such as pH, EC, DO, ORP, Salinity, TDS, BOD, COD, Hardness and Temperature. Eichornia crassipus shows maximum decrease in pH, TDS and COD and Lemna minor shows maximum decrease in EC, ORP, Salinity, BOD and TH. In case of DO maximum decrease was observed in control experiment. During the assessment period Lemna minor was found highly efficient in comparison to Eichornia crassipus. Both water hyacinth (Eichornia crassipus) and Duckweed (Lemna minor) shows maximum removal between 1st to 5th day of treatment but the removal goes down as the experiment proceeds towards the end as the retarded growth of plants was observed due to toxicity of accumulated pollutants inside the palnts.